Virtual Contract Analysis In E-Commerce: Maqaṣid Al-Shari'ah Perspective And The Relevance Of Dsn-MUI Fatwa No. 146/2021 - Ita Marianingsih; M. Ilham Zainullah; Muzanni Muzanni (STAI Al-Mas'udiyah, 2026)
This research aims to explore the validity and implications of virtual contracts in e-commerce through the lens of Maqaṣid al-Shari'ah, focusing on the application of Fatwa DSN-MUI No. 146/2021. The study investigates the alignment of digital contracts with Islamic principles, ensuring compliance with Shari'ah law in the digital economy. A qualitative approach, combining literature review and content analysis, is used to examine relevant fatwas, Maqaṣid al-Shari'ah theories, and the legal implications of virtual contracts in e-commerce. The study highlights the importance of ensuring that digital transactions uphold fairness, transparency, and Islamic ethical standards. It discusses the potential challenges and benefits of integrating Islamic law into e-commerce, with particular reference to Fatwa DSN-MUI No. 146/2021. The research provides insights into how businesses and consumers can implement Shari'ah-compliant e-commerce practices, fostering trust and contributing to the ethical development of the digital marketplace. This study bridges the gap in research by providing an in-depth analysis of virtual contracts under Islamic law and their practical implications for stakeholders in the digital economy.